Penerapan Algoritma Greedy Dalam Penentuan Prioritas Pengerjaan Tugas Kuliah Mahasiswa - Naufal Fakhri; Julian, Ary Sigit; Augustin, Darryl Sandi; Mavanudin, Zhykwa Ceryl; Christian, Efrans (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
College assignments play a crucial role in enabling students to grasp course material and achieve learning objectives. However, the demands of completing assignments from multiple courses often leave students confused about prioritizing tasks. This can lead to suboptimal assignment completion and potentially lower the quality of learning. This research aims to assist students in effectively prioritizing college assignment completion using the greedy algorithm. This algorithm will aid students in creating optimal assignment scheduling by considering various factors such as deadlines and assignment difficulty. The research methodology employs simulation with diverse courses as variables and different weights, such as deadlines and assignment difficulty. Preliminary results indicate that the implementation of the greedy algorithm prioritizes assignment deadlines over assignment difficulty, potentially enhancing assignment completion efficiency, leading to more timely task completion and a reduction in student stress levels. The anticipated outcome of this research is to provide students with a method for completing college assignments more efficiently and effectively. This could contribute to improving learning quality and achieving positive learning outcomes. By adopting this approach, students can directly benefit from the research in their academic lives, reducing stress and enhancing their productivity.